Questions as a Teaching Strategy to Develop Learning Capacity and Creativity - Vorobiova, Tatiana; Воробйова, Татьяна (My University, 2013)
This study surveyed the perception of questioning techniques by teachers as the key strategy for developing of learning capacity and creativity in the classroom. The article analyzes different approaches to classification of question types used in actual classes. The author focuses on the importance of using the questioning strategies and their effect on the academic achievements of students. The study presents a reasoned argument and complex citation and discus-sion of sources by both foreign and Ukrainian scholars. Various taxonomies of question forms and types, and response dimension of questions have been considered and a conceptual framework of questions has been developed to assess psychological processes underlying questioning strategy. It has been proved in the article that the teacher who incor-porates questions effectively by knowing the various purposes, types, and intended outcomes, establishes a classroom climate that promotes active engagement of pupils and thus encourages them to think critically and be creative.В статье исследуется одна из ключевых стратегий развития крити-ческого мышления и креативности младших школьников − вопросительная деятельность. Анализируются различные подходы к классификации типов вопросов, используемых для активизации учебного процесса. В центре внимания исследования − влияние этих технологий на академический прогресс учащихся. Всесторон-ний анализ источниковой базы, представленной как зарубежными, так и отечественными авторами, формирует методологическую базу исследования. В статье представлены разнообразные таксономии вопросов, концеп-туальные подходы к методике «вопросы− ответы»; рассматриваются системы вопросов, их последовательность. Доказано, что только тот учитель, который использует вопросительную технологию профессионально, создает положительный, комфортный климат в аудитории и, таким образом, ободряет и поощряет учащихся задавать вопросы, создавая проблемные ситуации и, благодаря этому, они приобретают первичный познавательно-творческий опыт.
Вопросительная деятельность как учебная стратегия развития способностей и креативности младших школьников
Keywords: critical thinking, effective dialogue, questions, questioning technique, teaching strategy, taxonomy.; вопросы, вопросительная стратегия/технология, таксономия, эффективный диалог, критическое мышление